Deciding the fate of the false Mott transition in two dimensions by exact quantum Monte Carlo methods. (September 2015) - Rost, D; Blümer, N
Abstract: We present an algorithm for the computation of unbiased Green functions and selfenergies for quantum lattice models, free from systematic errors and valid in the thermodynamic limit. The method combines direct lattice simulations using the Blankenbecler-Scalapino-Sugar quantum Monte Carlo (BSS-QMC) approach with controlled multigrid extrapolation techniques. We show that the half-filled Hubbard model is insulating at low temperatures even in the weak- coupling regime; the previously claimed Mott transition at intermediate coupling does not exist.